PAKISTAN-INDIA CONFLICT AND THE RIGHT OF SELF-DETERMINATION OF KASHMIR - Yordan Gunawan; Desi Nur Cahya Kusuma Putri; Ravenska Marchdiva Sienda; Sigit Rosidi; Ami Cintia Melinda (Fakultas Hukum, Universitas Diponegoro, 2021)
The dispute in Jammu and Kashmir has been tensed by the revocation of Article 370 of the Indian Constitution by the Indian government in the end of 2019. The existence of Kashmir has become one of matters as the main focus between India-Pakistan conflicts. People are under diverse senses of de facto and de jure martial law. Estimated from 1990, thereabouts 70,000 people have been killed, 8,000 people have been subjected to enforced disappearances, thousand of them also victims of repressive laws and Indian security forces humiliate the protestors and detainees frequently. The research is normative legal research by using statute approach and case approach through literature review. The research aims to discuss and analyze the implementation of the rights of self-determination pursuant to Kashmir dispute between India and Pakistan. The results of the study indicate all the disputes should be ended by giving the right to self-determination, which should be given to the people of Kashmir, thus the disputes between the two countries can be resolved properly and making a clarity of Kashmir status.